Contributions of the rodent cingulate-retrosplenial cortical axis to associative learning and memory: A proposed circuit for persistent memory maintenance. (November 2021) - Trask, Sydney; Ferrara, Nicole C.; Jasnow, Aaron M.; Kwapis, Janine L.
Highlights: The anterior cingulate and retrosplenial cortices are both involved in associative memory formation and recall. The anterior cingulate cortex seems to be specific to imprecise or generalized memories. The role of retrosplenial cortex does not change over time. The ACC and RSC likely interact to promote formation and long-term maintenance of associative memory. Abstract: While the anterior cingulate (ACC) and retrosplenial (RSC) cortices have been extensively studied for their role in spatial navigation, less is known about how they contribute to associative learning and later memory recall. The limited work that has been conducted on this topic suggests that each of these cortical regions makes distinct, but similar contributions to associative learning and memory. Here, we review evidence from the rodent literature demonstrating that while ACC activity seems to be necessary at remote time points associated with imprecise or generalized memories, the role of the RSC seems to be uniform over time. Together, the lines of evidence reviewed here suggest that the ACC and RSC likely function together to support memory formation and maintenance following associative learning.